Quercetin (3,3 ',4 ',5,7-pentahydroxyflavone) complexes with calcium(II) and magnesium(II), its potentiometric and spectrophotometric studies - (:unkn) unknown (WALTER DE GRUYTER GMBH, 2005)
In this study, the stability constants of the complexes of quercetin formed with calcium(II) and magnesium(II) were determined potentiometrically by using Calvin-Bjerrum and Irving Rossotti methods and by spectrophotometry. The evaluated protonation constants of the ligand were found: logK(1) = 9.63 +/- 0.11 and logK(2) = 8.32 +/- 013, at the 25 degrees C. For the calcium and magnesium complexes logarithms of the stability constants were found: for Ca : logK = 2.91 +/- 0.04, and for Magnesium: logK = 3.51 +/- 0.07. From the results, the components of quercetin-metal complexes are given 1:1 (quercetin:metal ratio) both Ca(II) and Mg(II).
Keywords: quercetin; magnesium; calcium; stability constant; potentiometri; spectrophotometri; CONSTANTS; PLASMA